EVALUATIVE STUDY FOR THE DEVELOPMENT OF LAND SPORTS ACHIEVEMENT IN NATIONAL PARALYMPIC COMMITTEE (NPC) SRAGEN FROM 2011 - 2018 - Januar Abdilah Santoso; Julianur Julianur; Jeane Betty Kurnia Jusuf; Nanda Alfian Mahardhika (Universitas Muhammadiyah Kalimantan Timur, 2019)
The purpose of this study was to find out: (1) the level of community needs for achievement coaching. (2) environmental support. (3) characteristics of athletes. (4) the characteristics of the trainer. (5) characteristics of the organizing organization. (6) the characteristics of the program and the basic strategy of NPC archery sports achievement development. (7) characteristics of the training program. (8) characteristics of facilities and infrastructure. (9) funding characteristics. (10) selection of athletes and coaches. (11) exercise. (12) exercise evaluation. (13) organizing coaching. (14) achievements of the archipelago NPC athletes.This research is a quantitative-qualitative descriptive study, using two approaches namely qualitative and quantitative approaches. Observation, document analysis and interviews are methods used to collect qualitative data, while to obtain quantitative data using the CIPP method.The results of this study are the high needs of disabled people for the achievements of Sragen NPC. The support from the LGs to Sragen NPC is quite high by providing land and building grants for secretarial offices and giving the same bonus as normal athletes. NPC archery athletes are in good condition seen in terms of physical, mental and highly motivated. The trainer has fulfilled the specified qualifications and has a qualified experience, except that he cannot focus on training because his status is also a coach and athlete. For the organizational structure of Sragen NPC it is well structured. Organizations have programs and strategies to achieve existing goals by coordinating with relevant agencies to get HR support both athletes and coaches, funding, sarpras, and prioritizing potential athletes on certain numbers. The training program has been implemented by the coach for his athletes, unfortunately there are no written documents. The training infrastructure is in Diponegoro Gor and training facilities such as bow and arrow are private property. NPC funding was obtained from KONI from the Sragen regency budget. Recruitment is in accordance with the procedures for implementing the center, because there is selection in recruiting athletes and coaches. The exercise of the trainer provides an exercise program that emphasizes the skills of each athlete, and pays attention to the physical, technical and mental development of the athlete but the trainer makes the training program adjust the situation and the training program has not been recorded. Evaluation is carried out every exercise by the trainer and colleagues verbally and not yet recorded. The State of the Organization of NPC Sragen runs well and Every HR in the Organizational Structure carries out its duties according to the job description of each.